Analisa Hubungan Intensitas Persaingan, Ukuran Perusahaan, dan Organisasi Pembelajaran dengan Penggunaan Sistem Informasi Akuntansi Pada Sektor Industri Manufaktur di Surabaya - Tanrim, Budi (Business Accounting Review, 2013)
This study aimed to analyze the relationship between the intensity competitiveness, firm size, learning organization with the use of Accounting Information System (AIS). AIS has an important role to support a company can excel in high competition by providing valid data for management decision making. Moreover, the larger the size of company the larger the needs to support the routine AIS remained firm in running productivity. The learning organization also needed by a company in order to be able to continue to compete in an environment that is constantly changing. On other hand the learning organization requires AIS as organizational memory to store the information obtained. Data were obtained through a questionnaire distributed to 63 managers and 37 owners of a manufacturing company in Surabaya. The data were processed by using the product moment correlation. The results showed that the variables of intensity of the company, firm size, and organizational learning have a significant relationship with the use of AIS. In addition, it was found that many of the manufacturing industries in Surabaya using SIA for external side (Financial Reporting System).